“Authentic” Modern American Painting and a Pioneering Painting During the Transition to Postmodern Art: Barnett Newman’s Onement I - Ö. Eren Koyunoğlu (Sanat Tarihi Yıllığı)
This study provides an overview of the development of an “authentic” American modern painting, focussing on Barnett Newman and his painting Onement I. It traces the evolution of American art with European influences, highlighting key events such as the introduction of American Impressionism and the 1913 International Exhibition of Modern Art. Later, it explores the emergence of “American Abstract Expressionism”, representing authentic American modern art, within the context of post-World War II, emphasising its connexion to American values of freedom and individualism. It also highlights the roles of art critics Harold Rosenberg and Clement Greenberg within the creation of American Abstract Expressionism, with Rosenberg emphasising action painting and Greenberg focussing on formalist criticism. At this point, problematics in the Turkish terminology of the field are also addressed.The development of American modern painting reached its final stage in “Post-Painterly Abstraction”, which abandoned the painterly trace of the artist’s elements in abstract art. Barnett Newman’s Onement I align with Greenberg’s views challenging traditional aesthetics and emphasising paint’s physicality, evoking the sublime. However, what distinguishes Onement I is its unique emphasis on prioritising the immediate visual experience for the viewer, marking a departure from the traditionally introspective nature of the artist’s inner world and aligning it with the principles of Post-Painterly Abstraction. This was a shift from artist-centred to viewer-focussed art, with Onement I serving as a pivotal turning point. Thus, this painting established the origins of Post-Painterly Abstraction and marked an important evolution in American modern painting. This also signifies a transition from modern art to postmodern art, with Onement I serving as a bridge between American Abstract Expressionism and this emerging artistic era.